1991
DOI: 10.1002/jbm.820250108
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of poly(sodium vinyl sulfonate) and its surface graft with antithrombin III

Abstract: Poly(sodium vinyl sulfonate) (PVS) was found to be 1/14 times as active as heparin in inducing the conformational change and activation of antithrombin III. The conformational change of antithrombin III was investigated in terms of the intrinsic fluorescence of tryptophan residue, the extrinsic fluorescence using 1,6-diphenyl-1,3,5-hexatriene as fluorescent probe, and Fourier-transform infrared spectroscopy. It was evident in the experiment using 2,4,6-trinitrobenzene sulfonate that PVS elicited the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…pVS has been explored before as an antithrombogenic agent, , HIV-inhibitor, coatings for antibacterial surfaces, and as polyelectrolytes for antibody and protein purification processes, but never before as a coactivator for FGFRs. From screening studies, we identified pVS from other polysulfonated polymers as a new heparin-mimicking polymer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…pVS has been explored before as an antithrombogenic agent, , HIV-inhibitor, coatings for antibacterial surfaces, and as polyelectrolytes for antibody and protein purification processes, but never before as a coactivator for FGFRs. From screening studies, we identified pVS from other polysulfonated polymers as a new heparin-mimicking polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Various concentrations of pVS 80.3 kDa were incubated with HDF cells in the absence of bFGF for 24 h. Then a LIVE/DEAD viability/cytotoxicity assay was performed, which indicated that the polymer was not toxic to HDF cells up to at least 1 mg/mL. pVS has been explored before as an antithrombogenic agent, 37,38 HIV-inhibitor, 39 coatings for antibacterial surfaces, 40 and as polyelectrolytes for antibody and protein purification processes, 41−43 but never before as a coactivator for FGFRs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The amount of primary amine introduced into the HA chains was determined by spectrophotometric methods 20. Samples were reacted with 2,4,6,‐trinitrobenzenesulfonic acid (TNBS; Sigma) in 4% NaHCO 3 , pH 8.5, at 40°C for 4 h and neutralized to pH 7.0.…”
Section: Methodsmentioning
confidence: 99%
“…Heparin is a natural polyanionic polysaccharide carrying sulfonate groups ( , ). Therefore, several investigations using sulfonated polymers have been performed ( ). Recently, it has been found that sulfated hyaluronic acid has a heparin-like property ( ).…”
Section: Introductionmentioning
confidence: 99%